Effects of sodium acetate supplementation on hematologic parameter, carbohydrate metabolism and intestinal microbiota of juvenile Micropterus salmoides fed high carbohydrate diets - Pengwei Xun; Hanjun Jiang; Qianqian Huang; Dexiang Feng; Feng Lun; Keng Yang; Xiaonian Wang; Yang Xiao; Sirui Jiao; Xusheng Guo; Wei Yu (Aquaculture Reports)
The study aims to identify the influences of sodium acetate on the growth, hematologic parameter, carbohydrate metabolism and gut microbiota of largemouth bass (Micropterus salmoides) fed high carbohydrate diets. The trial diets were formulated including the suitable carbohydrate (9 %, SC), the high carbohydrate (18 %, HCD) and HCD supplemented with 0.15 % sodium acetate (HCSD), and fed M. salmoides (initial body weight: 3.70 ± 0.06 g) for 8 weeks. The overcomes demonstrated compared to the SC group, the fish fed HCD exhibited metabolic abnormalities and liver damage accompanied with high levels of glucose (GLU), hepatosomatic index (HSI), aspartate aminotransferase (AST) and hepatic glycogen as well as high activities of phosphoenolpyruvate carboxykinase (PEPCK) and glucose 6 phosphatase (G6P). However, inclusion of sodium acetate promoted the growth performance and lowered blood GLU and liver glycogen levels. Moreover, adding sodium acetate inhibited gluconeogenesis and promoted glycolysis via the Adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK) pathway. Additionally, in comparison with the HCD group, sodium acetate supplementation improved the composition of gut microbiota, inhibited the proportion of pathogens (Acinetobacter, Mycoplasma, Pseudomonas and Sediminibacterium) and increased the abundance of beneficial bacteria (Cetobacterium and Romboutsia). We concluded that sodium acetate mitigated effectively the adverse symptoms of M. salmoides fed HCD. More importantly, sodium acetate addition may improve the carbohydrate utilization by increasing the proportion of intestinal Cetobacterium and Romboutsia.